2020
DOI: 10.1016/j.eclinm.2020.100375
|View full text |Cite
|
Sign up to set email alerts
|

Eosinopenia and elevated C-reactive protein facilitate triage of COVID-19 patients in fever clinic: A retrospective case-control study

Abstract: Background: Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently a pandemic affecting over 200 countries. Many cities have established designated fever clinics to triage suspected COVID-19 patients from other patients with similar symptoms. However, given the limited availability of the nucleic acid test as well as long waiting time for both the test and radiographic examination, the quarantine or therapeutic decisions for a large number of mixed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
170
7
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(199 citation statements)
references
References 19 publications
18
170
7
4
Order By: Relevance
“…Demographic data and clinical characteristics of COVID+ pediatric patients (data updated on April 16) patients, having eosinophilia, are less affected by COVID-19. The literature data could support this theory [5][6][7]. Consistently, we found only two allergic children (food allergy and allergic rhinitis) and one child with asthma.…”
supporting
confidence: 88%
“…Demographic data and clinical characteristics of COVID+ pediatric patients (data updated on April 16) patients, having eosinophilia, are less affected by COVID-19. The literature data could support this theory [5][6][7]. Consistently, we found only two allergic children (food allergy and allergic rhinitis) and one child with asthma.…”
supporting
confidence: 88%
“…When eosinophils are combined with lymphocytes, the diagnosis effect has higher AUC and speci city. This result is consistent with previous research [14], which demonstrated that eosinophils count is helpful to speed up diagnosis for COVID-19 patients, especially in combination with lymphocyte count.…”
Section: Relationship Between Recovery Of Eosinophil Count and Patiensupporting
confidence: 93%
“…As several studies already examined the influence of COVID-19 on routine hematology parameters in their country [3][4][5][6][7][8][9][10][11][12][13], the aim of this study was to confirm or reject these findings in our hospital and to investigate whether there is a specific time period after disease onset in which predictions of outcome can be made based on routine hematology parameters.…”
Section: Introductionmentioning
confidence: 96%